2021
DOI: 10.3389/fnmol.2021.720984
|View full text |Cite
|
Sign up to set email alerts
|

GRIN2A Variants Associated With Idiopathic Generalized Epilepsies

Abstract: Objective: The objective of this study is to explore the role of GRIN2A gene in idiopathic generalized epilepsies and the potential underlying mechanism for phenotypic variation.Methods: Whole-exome sequencing was performed in a cohort of 88 patients with idiopathic generalized epilepsies. Electro-physiological alterations of the recombinant N-methyl-D-aspartate receptors (NMDARs) containing GluN2A mutants were examined using two-electrode voltage-clamp recordings. The alterations of protein expression were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 75 publications
0
15
0
Order By: Relevance
“…7 Subsequently, the clinical phenotype in a patient is usually a part of the spectrum. In the CCE, the phenotype of varied severity should be explained by the implication of the variant, such as the nature, functional consequence, and sub-molecular effect of the variant 16,18 . The MAF is critical in considering the pathogenicity/causality of a variant and was taken into the criterion of severity concordance evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Subsequently, the clinical phenotype in a patient is usually a part of the spectrum. In the CCE, the phenotype of varied severity should be explained by the implication of the variant, such as the nature, functional consequence, and sub-molecular effect of the variant 16,18 . The MAF is critical in considering the pathogenicity/causality of a variant and was taken into the criterion of severity concordance evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…After excessed the GDQ, the damages of variants are quantitatively correlated with the pathogenicity and potentially associated with a phenotype spectrum of varying severity 7 (Figure 1). The severity concordance is considered on: 1) genotypeseverity correlation; in genes featured by LOF, destructive variant generally causes severer biochemical consequence on structure/function than missense variant and subsequently is associated with severer phenotype; however, missense variants are also possible to be associated with severer phenotype than destructive variants in some genes due to special mechanisms; 15 2) funotype-phenotype correlation; for genes with multiple pathogenic funotypes, different funotypes, such as LOF and GOF, may be associated with phenotypes of different severity; 11 3) quantitative correlation between functional alteration and phenotype severity demonstrated by functional studies, such as that in GRIN2A; 16 4) molecular sub-region effect of missense variants, which was associated with phenotype severity as indicated in previous studies; 17,18 5) monoallelic/bi-allelic variants, or heterozygous/hemizygous variant, in genes associated with both dominant and recessive inheritances, with considerations also on the genotype (Figure 1); and 6) other evidence such as the length of abnormal trinucleotide expansion correlated with phenotype severity. 14 The CCE contains three supporting criteria: 1) in pathogenic genes that are potentially associated with a phenotype of relatively consistent in severity, the phenotype of consistent severity is observed in the patient; 2) in genes that are associated with a phenotype spectrum of varied severity implication of the variant explains varied severity in the patient; 3) con rmed pathogenic variants (or genotype), including those with varied phenotypes.…”
Section: Establishment Of the Cce Frameworkmentioning
confidence: 99%
“…The functional consequence of variants includes loss of function that is indicated by identi cation of null (destructive) variants and pathogenic funotypes (functional alterations) 3 that are experimentally determined for other kinds of variants, especially missense ( c). Correlations between functional impairment and phenotype, including funotype-phenotype correlation 3,21 and quantitative correlation between functional impairment and phenotype severity 22 , are supportive of gene-disease association ( d).…”
Section: Functional (Experimental) Pro Lementioning
confidence: 95%
“…Where in a gene a variant is located can affect the mechanism of disease, as well as penetrance and expressivity through molecular subregional effects ( Platzer et al, 2017 ); the impact of a variant depends on whether it is located at sites that undergo post-translational modification, within sites that are critical for tertiary and quaternary structure, at protein–protein interaction interfaces or ligand binding sites, or inside versus outside of functional domains ( Faure et al, 2022 ). For example, missense variants in GRIN2A located in transmembrane or linker domains were more frequently associated with severe developmental phenotypes than those located elsewhere, such as within amino-terminal or ligand-binding domains ( Liu et al, 2021 ), with a wide range of phenotypes observed from normal to mild epilepsy, to severe developmental phenotypes and epileptic encephalopathy ( Strehlow et al, 2019 ); similarly, GoF variants in highly conserved regions of the potassium channel of KCNA2 were associated with more severe epileptic encephalopathy than variants located elsewhere ( Masnada et al, 2017 ). An improved understanding of the protein structure and the functionality of interacting domains will help elucidate specific variant effects on the resulting phenotypic presentation ( Ittisoponpisan et al, 2021 ).…”
Section: Causal Variantsmentioning
confidence: 99%